Organising under the Revolution : Unions and the State in Java, 1945‒48 - Suryomenggolo, Jafar, 1978- (Book collections on Project MUSE., 2013)
The years 1945-48 marked the peak of the Indonesian revolution, but they were also formative years for state-labour relationship in Indonesia. Drawing on a range of historical sources, the author reconstructs labour's initial drive to form and orient unions during this critical period. The historical narrative captures early unions' nationalist spirit and efforts to defend members' socio-economic interests, and shows the steps taken by the labour movement to maintain its independence and build institutional capacity within the new Indonesia state.